Hubungan Tingkat Pengetahuan Dan Sikappetugas Kesehatan Dengan Penerapan Teknik Mencuci Tangan Secara Benar - Eni - Purwanti; Darwin - Karim; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aims to determine the relationship of the level of knowledge and attitude of health service worker’s with the application of correct hand washing techniques. The method used is the descriptivecorrelative. This research was conducted emergency room of Arifin Achmad Hospital in Pekanbaru with 41 respondents. Measuring instrument used was a questionnaire. Data were analyzed by using chi-square with the confidence level = 0.05. The results showed that there is a relationship between health service worker’s knowledge of the application of attitude hand washing techniques with ​​p value = 0.016. The results also show that there is a relationship between health worker’s attitudes with the application of proper hand washing techniques with p value = 0.006. It is suggested for health service worker’s in Arifin Achmad Hospital are expected to maintain and improve knowledge and attitudes appropriate hand washing procedures set correctly. Key words : Knowledge, Attitude, Health Service Worker’s , Hand Washing Techniques Properly